2007
DOI: 10.1152/ajpregu.00442.2007
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle work in acute hypoxia influences locomotor muscle fatigue and exercise performance of healthy humans

Abstract: Our aim was to isolate the independent effects of 1) inspiratory muscle work (Wb) and 2) arterial hypoxemia during heavy-intensity exercise in acute hypoxia on locomotor muscle fatigue. Eight cyclists exercised to exhaustion in hypoxia [inspired O2 fraction (FIO 2 ) ϭ 0.15, arterial hemoglobin saturation (SaO 2 ) ϭ 81 Ϯ 1%; 8.6 Ϯ 0.5 min, 273 Ϯ 6 W; Hypoxia-control (Ctrl)] and at the same work rate and duration in normoxia (SaO 2 ϭ 95 Ϯ 1%; Normoxia-Ctrl). These trials were repeated, but with a 35-80% reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 64 publications
1
122
2
Order By: Relevance
“…because of the difficulty of maintaining the same intensities as at sea level. 35 In our case, the execution of squat jumps were technically maintained and performed equally by both groups.…”
Section: Discussionmentioning
confidence: 83%
“…because of the difficulty of maintaining the same intensities as at sea level. 35 In our case, the execution of squat jumps were technically maintained and performed equally by both groups.…”
Section: Discussionmentioning
confidence: 83%
“…By changing FI O 2 and/or the work of breathing (by using pressure-assisted ventilation) during exercise, it has been demonstrated that the increased work of breathing during hypoxic exercise independently enhances locomotor muscle fatigue during cycling, probably by reducing blood flow to the legs (9). Given these results, it can be hypothesized that brain perfusion during high-intensity hypoxic exercise might be compromised by 1) competition for blood flow distribution in face of increased locomotor muscle perfusion compensating for reduced arterial oxygenation (17), and 2) the increased work of breathing potentially impairing blood flow to other regions of the body (9). In support, greater alteration in brain versus muscle oxygenation (as determined by NIRS) in hypoxia compared with normoxia was reported during rest and exercise (2,102), leading the authors to suggest that a "steal" of blood from cerebral circulation to the muscle may occur in hypoxia.…”
Section: Concurrence For Blood Flowmentioning
confidence: 99%
“…Exercise in hypoxia would also be expected to exacerbate the effects of respiratory muscle work on limb fatigue and exercise tolerance. Recent evidence suggests that the increased work of breathing during acute moderate hypoxia (arterial O 2 saturation 81%) accounts for at least one-third of the total limb locomotor muscle fatigue induced by exercise and a significant part of the hypoxia-induced reduction in exercise tolerance (8). The effects of augmented respiratory muscle work in acute hypoxia on limb fatigue and exercise tolerance may be especially significant in chronic hypoxia during which the hyperventilatory response and work of breathing are greatly magnified (129).…”
Section: Conditions Under Which Respiratory Muscle Work Affects Limb mentioning
confidence: 99%